1995
DOI: 10.1177/153331759501000406
|View full text |Cite
|
Sign up to set email alerts
|

An examination of a proposed scoring procedure for the clock drawing test: Reliability and predictive validity of the clock scoring system (CSS)

Abstract: The clock drawing test (CDT) is usedfor a variety of diagnostic purposes, including screening for dementia. Individuals have relied on subjective judgments in distinguishing between normal and abnormal clocks. This studyproposesaformal, objective scoring procedure called the Clock Scoring System (CSS). The CDTwas administered to 23 dementia patients and 27 normal, elderly controls. The inter-rater reliability estimates of the CSS rangedfrom 82 to .98 across diagnostic groups. Scores discriminated between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…The 4 scoring systems (Freedman et al [15] , Rouleau et al [16] , Todd et al [17] , and the CERAD CDT [18] ) lack sensitivity in distinguishing the MCI group from the NCI group. The sensitivity for detecting individuals with MCI was so poor that quantitative analysis of the CDT does not appear to be a good screening instrument for detecting MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 scoring systems (Freedman et al [15] , Rouleau et al [16] , Todd et al [17] , and the CERAD CDT [18] ) lack sensitivity in distinguishing the MCI group from the NCI group. The sensitivity for detecting individuals with MCI was so poor that quantitative analysis of the CDT does not appear to be a good screening instrument for detecting MCI.…”
Section: Discussionmentioning
confidence: 99%
“…The CDT was scored by a general physician according to the rating scales of Freedman et al [15] , Rouleau et al [16] , Todd et al [17] , and the CERAD CDT [18] for quantitative analysis, and a comprehensive CDT scoring system incorporating elements of most previous CDT for qualitative analysis [19] . The CDT scorer for the present study was not given any information about participants, including performance on other cognitive tests or clinical diagnosis.…”
Section: Measurementsmentioning
confidence: 99%
“…A modifi ed version of the Clock Scoring System (CSS) by Todd, Dammers, Adams, Todd, and Morrison ( 1995 ) was used for quantitative analysis (Detailed criteria for the modifi ed CSS are listed in Appendix 1 ). Qualitative error analyses of the CDT were performed using the criteria developed by Rouleau, Salmon, Butters, Kennedy, and McGuire ( 1992 ).…”
Section: The Clock Drawing Testmentioning
confidence: 99%
“…Although the screening utility of the CDT in dementia has been ascertained (Peters & Pinto, 2008), its utility in mild cognitive impairment (MCI) remains controversial. K. S. Lee et al (2008) investigated this issue using four scoring methods-namely, the Freedman et al (1994), the Rouleau, Salmon, Butters, Kennedy, and McGuire (1992), the Todd, Dammers, Adams, Todd, and Morrison (1995) methods and the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) method (J. H. Lee, Lee, & Lee, 2002). These authors found that the sensitivity and specificity values of these four quantitative scoring methods were not acceptable and concluded that although qualitative analyses (such as the analysis of error types) may help the identification of MCI patients, the CDT alone is not sufficient as a screening tool in this population.…”
mentioning
confidence: 99%